Jaringan Saraf Tiruan Memprediksi Tingkat Penjualan Smartphone Di Wijaya Cell Pematangsiantar Menggunakan Metode Backpropagation - Syahrial Azmi Pohan; M. Safii; Sundari Retno Andani; Muhammad Rafai; Abdi Rahim Damanik (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
This study aims to optimize profits and minimize losses from smartphone sales at Wijaya Cell stores that have been achieved in the future. The data used in this study were obtained directly from the Wijaya Cell store by conducting observations and interviews. The Wijaya Cell store is a communication technology that sells smartphones to be marketed to the public. The data that will be processed from the sale of the Wijaya Cell smartphone uses the Backprogation method which is an Artificial Neural Network. The data used is annual smartphone sales data from 2018-2021. From the results of research with training data experiments, it was found that the best architecture was 3-8-1 with 92% accuracy, MSE training was 0.0099974. It is concluded that the Backprogation method can be implemented in predicting smartphone sales results. By doing this research, it is hoped that it can provide input to the Wijaya Cell Shop in optimizing profits and minimizing losses from smartphone sales in the future